A Systematic Review of Health Outcomes Associated with Smoke Free Legislation: Evidence on Reducing Tobacco Related Diseases - Firmansyah (Jurnal Riset Kualitatif dan Promosi Kesehatan, 2023)
Smoke-free policies have emerged as a critical strategy in global public health, aimed at reducing smoking prevalence and mitigating the risks associated with secondhand smoke exposure. This study systematically reviews the effectiveness of smoke-free laws in reducing tobacco-related diseases, improving public health outcomes, and influencing smoking behaviors. A comprehensive literature search was conducted using PubMed, Scopus, and Web of Science to analyze empirical studies on smoke-free regulations over the past fifteen years. Findings indicate that smoke-free policies significantly reduce hospital admissions for respiratory and cardiovascular diseases, lower tobacco-related mortality, and enhance smoking cessation rates. The benefits are particularly notable among vulnerable populations, including children, pregnant women, and individuals with chronic health conditions. However, challenges in enforcement, compliance, and socio-economic disparities continue to affect policy efficacy. Regional variations demonstrate that cultural norms, economic stability, and community engagement play a critical role in shaping policy effectiveness. To maximize public health benefits, policymakers should focus on strengthening legislative enforcement, increasing public awareness through educational initiatives, and addressing socio-economic barriers to compliance. Future research should explore the long-term effects of these policies and develop targeted interventions that integrate public health advocacy with economic incentives. Implementing comprehensive, well-enforced smoke-free policies is essential for reducing tobacco-related disease burdens and fostering healthier environments globally.